2009
DOI: 10.2190/ic.29.1.e
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Patterns, Personality, and Subjective Anomalous Experiences

Abstract: An opportunity sample comprising 281 participants completed a battery of questionnaires, which included questions on sleep, the Anomalous Experience Inventory [1], the STA scale (for measurement of positive schizotypy) [2], the Complex Partial Epileptic-like signs scale of the Personal Philosophy Inventory [3], Hartmann's Short Boundary Questionnaire (BQ) [4], and the revised Transliminality scale [5]. There was no difference between long and short sleepers on anomalous experiences. All personality variables c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
2
1
2
Order By: Relevance
“…As noted previously, the possibility exists that self-selection biases produced a sample that overrepresented individuals with active interests in ExEs. Descriptive statistics for the AES were slightly higher in our study ( M = 10.23) than in a prior survey based on a general population sample ( M = 7.5; Simmonds-Moore, 2009), and therefore may have overrepresented the frequencies of synesthetic experiences. Our findings thus require replication in more representative random samples.…”
Section: Discussioncontrasting
confidence: 88%
“…As noted previously, the possibility exists that self-selection biases produced a sample that overrepresented individuals with active interests in ExEs. Descriptive statistics for the AES were slightly higher in our study ( M = 10.23) than in a prior survey based on a general population sample ( M = 7.5; Simmonds-Moore, 2009), and therefore may have overrepresented the frequencies of synesthetic experiences. Our findings thus require replication in more representative random samples.…”
Section: Discussioncontrasting
confidence: 88%
“…De todos modos, futuros estudios deberían examinar cómo exactamente funciona esta hiperconectividad o sensibilidad ambiental para producir tales experiencias. El concepto de límite fi no podría refl ejar un sistema holárquico (Simmonds-Moore, 2009, 2016. El aspecto biológico del límite fi no permite diferentes propiedades de la sensibilidad en niveles cada vez más altos (o integrados), y, como tal, la mente es dependiente de procesos físicos más que la suma de partes (Fleck et al, 2008).…”
Section: Discussionunclassified
“…In terms of diurnal hypnagogic experiences, one study found that hypnagogic experiences peak in the late afternoon (3:11 p.m. and 4:02 p.m.; Nielsen, 1995). We suggest that if an experiment is run in the afternoon or evening, the likelihood of experiencing a shift in consciousness (hypnagogia) and potentially an ExE could be increased anyway because of circadian and ultradian rhythms (Simmonds-Moore, 2009). For example, 4 p.m. falls within the circasemidian nadir , which reflects a period in the biological rhythm when it is more likely that a person will fall asleep (Nielsen, 1991–1992).…”
Section: Alternative and Complementary Explanationsmentioning
confidence: 99%